ACCOUNTING REPORTS AS SOURCE OF ECONOMIC INFORMATION - O. Dyakonova; N. Morgun (Вестник университета)
In this article importance of accounting (financial) control is examined as a source of many economic indicators of activity of enterprise. Basic analytical indexes, order of their calculation, possible interpretations, influence on judgment of users of accounting (financial) control, are enumerated.